A hybrid direct-absorption parabolic-trough solar collector combining both volumetric and surface absorption. (25th February 2021) - Qin, Caiyan; Lee, Jungchul; Lee, Bong Jae
Abstract: By making the nanofluids separately flowing into two concentric segmentations in a direct-absorption parabolic-trough solar collector (DAPTSC), we recently showed that the dual-nanofluid DAPTSC with a semi-cylindrical reflective coating could reduce the heat loss to the environment by employing the nanofluid of lower concentration in the outer section while the nanofluid of a higher concentration in the inner section. In this work, we propose to replace the semi-cylindrical reflective coating with a semi-cylindrical absorbing coating for exploiting both volumetric and surface absorption of the solar radiation. It is shown that the DAPTSC with a hybrid of volumetric and surface absorption can achieve a significantly higher thermal efficiency than the previous design of a DAPTSC with a reflective coating, especially when the absorption coefficients of the nanofluids are low. This opens a new opportunity of further reducing the nanoparticle concentration in a DAPTSC. Highlights: A semi-cylindrical absorbing coating is applied to a dual-nanofluid DAPTSC. The absorbing coating improves the solar absorption and reduces heat loss to surrounding. A hybrid DAPTSC outperforms other configurations in a wide temperature range. The proposed design opens a new opportunity of further reducing the nanoparticle concentration.